Training On Making "Soybean Tempe" To Increase Family Income For Local Housewives In Silalas Village, Medan - Lusiah Lusiah; Edison Parulian; Lenny Menara Sari Saragih; Tarwiyah Tarwiyah; Corinna Wongsosudono (International Journal Of Community Service, 2023)
This activity is a partnership-based UMKM development program wherethis program provides activities to provide tempe training to housewiveslocated in Silalas Village, West Medan by bringing in resource personswho are UMKM assisted by the UMKM development program who alsoact as mentors for community members, especially mothers. households inthe Silalas Village environment to foster entrepreneurial interest andprovide ideas for business activities that can be carried out so as toimprove the family's economy. Apart from that, the resource person canalso share tips for successfully running a business using enthusiasm,tenacity and perseverance with housewives.